DOLENKUY.COM: PLATFORM DIGITAL SEBAGAI VIRTUAL TOURISMDAN E-MARKETPLACEUNTUK MENDUKUNG EKONOMI PARIWISATA DAN UMKM PADA MASA PANDEMI COVID-19 - Rizki, Iqbal Ainur; Saputri, Aulia Dwi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
The Covid-19 pandemic has had a negative impact on the business sector, MSMEs, and the tourism sector which had to experience a decline in income during this Covid-19 pandemic. One of the affected areas is Mojokerto Regency. Mojokerto Regency has many tourism sectors that are known by everyone. Based on these problems, a solution is needed that can overcome economic problems in the tourism sector and MSMEs in Mojokerto. The purpose of writing this paper is to describe the concepts and features on Dolenkuy.com, analyze the predictions of the advantages and success of the Dolenkuy.com platform, and analyze the implementation techniques of the Dolenkuy.com platform. The research method used in this paper is a literature study and uses a descriptive writing method with a qualitative approach. From the writing of this paper, it is found that Dolenkuy.com is an innovation in the form of a website-based digital platform that functions as a virtual tourism and e-market place during the Covid-19 pandemic era. The features found on this platform are virtual dolen menu, buying souvenirs, travel history, to the contact us menu. This platform is predicted to excel in the fields of digitizing tourism and MSMEs, income, marketing, superior locations and products, as well as a wide range of tourists. And the last is the implementation technique of this platform starting from the problem identification stage to the platform evaluation and development stage with an estimated implementation time of 5.5 months.